Gender, the Cold War, and Ingeborg Bachmann - Sara Lennox (Studies in 20th & 21st Century Literature, 2007)
This essay uses the methodology of materialist feminism to situate Ingeborg Bachmann's life and writing in their Cold War context. After outlining the ways in which U.S. Cold War policy affected Austrian cultural life in the nineteen-fifties, I show that Bachmann's own activities during the period of U.S. occupation were steeped in that Cold War atmosphere. I also argue that the Cold War reconfiguration of gender relations left their imprint on Bachmann's writing. Comparing the narrative techniques of the unpublished short story "Sterben für Berlin" (1961) and Bachmann's Büchner Prize Speech "Ein Ort für Zufälle" (1964), I maintain that both texts address the Cold War's impact on Central European subjectivity and that Bachmann's subsequent writing oscillates between those two narrative approaches. Particularly the middle, dream chapter of the novel Malina uses the expressionist or surrealist strategies of "Ein Ort für Zufälle" to present history only via the scars left on the psyche, what Bachmann called "die Geschichte im Ich." Subsequent to the novel Malina, the figure Malina assumes the narrative standpoint of "Sterben für Berlin" to tell the apparently realist stories of the "Todesarten" cycle, whose characters remain unaware of the social forces of which they are victims.
Keywords: materialist feminism; Ingeborg Bachmann; Cold War; U.S. Cold War; Austria; Austrian culture; gender relations; gender; Sterben für Berlin; Ein Ort für Zufälle; Malina; surrealism; expressionism; Todesarten